2021
DOI: 10.1111/jfpp.15375
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on rice flour and jaggery paste as food material for extrusion‐based 3D printing

Abstract: A novel 3D printable food construct, comprising of rice flour (RF), jaggery (J), and water (W) are being investigated for an extrusion‐based 3D food printer. The effect of the constituents on the rheological properties, textural properties, and printability of 20 different combinations were investigated and two combinations of R3 and R5 were found to be best printable based on their shape retention after printing. To determine the best combination between R3 and R5 steaming was done as post‐processing and R5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…e raw materials used in this study were rice flour, jaggery, and water. e paste used in the experiments was produced by the method enumerated by angalakshmi et al [9]. Rice grains were cleaned, washed, sun-dried, milled, and sieved through a 250-micron sieve.…”
Section: Paste Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…e raw materials used in this study were rice flour, jaggery, and water. e paste used in the experiments was produced by the method enumerated by angalakshmi et al [9]. Rice grains were cleaned, washed, sun-dried, milled, and sieved through a 250-micron sieve.…”
Section: Paste Preparationmentioning
confidence: 99%
“…In such cases, some additives are usually added to improve the printability of rice flour [5,7,8]. In this study, rice flour has been mixed with jaggery and water, which led to an improvement in the viscoelastic properties of the paste, making it suitable for 3D printing [9]. Jaggery can be used as a healthy alternative to sugar in 3D food printing [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The defatted BSFP flour can be used as replacement of existing flours for supplementation of protein and micronutrients. Recently there is a trend in utilization of novel flours as a functional ingredient in food products such as noodles, spaghetti, cookies, and extruded products (Öztürk & Turhan, 2020; Rungsardthong et al., 2021; Thangalakshmi et al., 2021). However, limited studies reported on the physicochemical and nutritional properties of BSFP flour.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the present research is planned to investigate the effect on the physicochemical properties, nutritional composition, structural integrity, and thermal stability of BSFP defatted flour during freeze‐ and sun‐drying. The study explore the impact of drying on BSFP flour, which depicts the feasibility in producing extruded foods, RTE, 3D‐printed foods with advantage of low‐fat flour substitute (Rungsardthong et al., 2021; Schweinberger et al., 2020; Senapati et al., 2017; Thangalakshmi et al., 2021).…”
Section: Introductionmentioning
confidence: 99%